Prevalence of Hypertension in Indonesia: 2018 Basic Health Research - Nafasha Fairly Ikhlasia; Inna Syafarina; Arnida L Latifah (Jurnal Kesehatan Masyarakat, 2025)
Hypertension is one of the main factors contributing to premature death. The nationwide prevalence rate of hypertension in Indonesia is relatively high. Understanding the factors contributing to hypertension is essential to reduce the prevalence of hypertension. This paper investigates the risk factors associated with hypertension based on the survey data of Riskesdas 2018. The risk factors related to behaviors or lifestyle include smoking every day, being less active, eating fatty or salty foods once a day, drinking caffeine once a day, and overweight status. Using multiple linear regression, this study finds that being overweight with a body mass index in range 25-27 and having a daily coffee intake habit of one cup are the most significant risk factors to the prevalence of hypertension. These findings should be used as a reference for preventative and promotional actions to reduce the prevalence of hypertension in Indonesia.